Parental treatment methods and their relationship to achievement motivation among a sample of gifted female students at the secondary stage in Jeddah - Al-Mabadi, Maram Hajjaj; BaAmer, Manal Yahya (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the methods of parental treatment and their relationship to motivation for achievement among a sample of gifted female students in the secondary stage in the city of Jeddah. The study included (31) female students who were randomly selected. The study followed the descriptive, correlational approach to find out the relationship between the methods of parental treatment and motivation for achievement. Two scales were used. To collect data, there is a measure of parental treatment methods as perceived by children, prepared by Faten Suleiman, and a measure of achievement motivation for adolescents, prepared by Othman and Shaheen. The data were statistically analyzed using statistical packages. The results showed that the permissive method is the most widespread and prevailing in parental treatment among the study sample, followed by the democratic method. It is followed by the authoritarian style. The results also show that the level of motivation to achieve has been achieved to a moderate degree among gifted female students in the city of Jeddah. In light of the results, the study presented a number of recommendations, including: The necessity of providing awareness to families, especially parents, about the importance of the treatment methods used with their children.
Keywords: methods of parental treatment; achievement motivation; gifted students; high school